Orbitofrontal and anterior cingulate cortex neurofibrillary tangle burden is associated with agitation in Alzheimer disease - (:unkn) unknown (My University, 2001)
Few studies evaluate neuropathological correlates of behavioral changes in Alzheimer disease (AD). We identified 31 autopsy patients with a diagnosis of definite AD. Behavioral changes were assessed with the Neuropsychiatric Inventory. Brain sections were collected from bilateral orbitofrontal and left anterior cingulate, superior temporal, inferior parietal, occipital, and hippocampal cortices for quantification of neurofibrillary tangles (NFTs) and diffuse and neuritic plaques. Sections from frontal, cingulate, and hippocampal cortices were reviewed for the presence of Lewy bodies (LBs). Hypothesis-driven correlational analyses were performed by the bootstrap method. Subgroup analyses contrasted a group with high scores of one specific behavior to a group with low scores after equating groups for other behaviors. NFT burden in the left orbitofrontal cortex across all 31 patients significantly correlated with agitation scores (r = 0.41, p < 0.015) and NFTs correlated significantly (r = 0.66, p = 0.004) with higher agitation scores in the subgroup analysis. Left anterior cingulate NFTs, although not within our hypotheses, also showed a significant relationship to agitation within the subgroups (r = 0.76, p = 0.0003; Bonferroni p = 0.02). Seven patients, including three in the agitation subgroup, had cortical LBs. Aberrant motor behavior and NFT density in the left orbitofrontal cortex showed a significant relationship for the entire group (r = 0.38, p < 0.03) and for subgroups (r = 0.49, p = 0.04), whereas apathy and left anterior cingulate NFTs showed a significant relationship only for the entire group (r = 0.25, p ≤ 0.01). These observations suggest that agitation and aberrant motor behavior are correlates of greater NFT pathology in the orbitofrontal cortex in AD, whereas increasing apathy may relate to greater NFT burden in the anterior cingulate.